Nickel electrode for alkaline secondary battery and alkaline secondary battery including said nickel electrode
Patent Information
- Application Number
- JP2022501778
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-21
- Filing Date
- 2021-02-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-02-04
AI Technical Summary
【0014】 本発明に係るアルカリ二次電池用のニッケル極は、正極芯材、及び前記正極芯材に充填されている正極合剤を備えており、前記正極合剤は、正極活物質である水酸化ニッケルを含み、前記水酸化ニッケルは、硫酸塩を含有しており、前記硫酸塩に含まれるS成分は、前記水酸化ニッケル中のNi成分に対する重量比率が、0.28%以上1.50%以下である。水酸化ニッケル中の硫酸塩に含まれるS成分が、Ni成分に対する重量比率で、0.28%以上1.50%以下であることにより、アルカリ二次電池のメモリ効果の影響を低減できる。このため、本発明によれば、メモリ効果の影響を低減できるアルカリ二次電池用のニッケル極、及びこのニッケル極を含むアルカリ二次電池を提供することができる。
Smart Images

Figure 0007643825000003 
Figure 0007643825000004 
Figure 0007643825000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a nickel electrode for an alkaline secondary battery, and to an alkaline secondary battery including the nickel electrode. [Background technology]
[0002] Nickel electrodes are generally used as positive electrodes in alkaline secondary batteries. Non-sintered nickel electrodes are widely used as such nickel electrodes. These non-sintered nickel electrodes are manufactured, for example, by filling a positive electrode active material slurry containing particles of nickel hydroxide, which is a positive electrode active material, into a foamed nickel (positive electrode core material) having a three-dimensional mesh structure, drying it, and then pressure molding it. This non-sintered nickel electrode allows for a larger amount of nickel hydroxide to be filled, so it has a larger capacity per unit volume, which contributes to increasing the capacity of alkaline secondary batteries.
[0003] Alkaline secondary batteries having high capacity achieved by using non-sintered nickel electrodes in this way are now being used in a wide variety of applications, such as various electronic devices, electric devices, and hybrid electric vehicles.
[0004] However, when alkaline secondary batteries are repeatedly charged and discharged, the actual usable charge capacity decreases due to the so-called memory effect. In particular, when a battery is repeatedly discharged to a shallow depth, the discharge voltage decreases and the discharge capacity decreases at that depth of discharge.
[0005] As a method for eliminating such a memory effect, a so-called refresh charge / discharge is known, in which a full charge is followed by a full discharge (see, for example, Patent Document 1, etc.). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2001-095167 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the above-mentioned refresh charge / discharge is not a fundamental solution since it does not prevent the occurrence of the memory effect.
[0008] In addition, in applications such as hybrid electric vehicles, upper and lower limits are set for the state of charge (SOC) to prevent overcharging and overdischarging, which makes it difficult to perform refresh charging and discharging in the first place, and therefore difficult to eliminate, prevent, or suppress the memory effect. Therefore, there is a need for the development of an alkaline secondary battery that is less susceptible to the memory effect.
[0009] The present invention has been made in light of the above circumstances, and has an object to provide a nickel electrode for an alkaline secondary battery capable of reducing the influence of the memory effect, and an alkaline secondary battery including this nickel electrode. [Means for solving the problem]
[0010] According to the present invention, there is provided a nickel electrode for an alkaline secondary battery, comprising a positive electrode core material, and a positive electrode mixture filled in the positive electrode core material, the positive electrode mixture containing nickel hydroxide as a positive electrode active material, the nickel hydroxide containing a sulfate, and an S component contained in the sulfate having a weight ratio of 0.28% or more and 1.50% or less relative to a Ni component in the nickel hydroxide.
[0011] The nickel hydroxide preferably contains Al as a solid solution element.
[0012] The present invention also provides an alkaline secondary battery comprising a container and an electrode group housed in the container together with an alkaline electrolyte, the electrode group including a positive electrode and a negative electrode combined with a separator interposed therebetween, the positive electrode being any of the nickel electrodes for use in the alkaline secondary batteries described above.
[0013] The negative electrode preferably contains a hydrogen storage alloy. Effect of the Invention
[0014] The nickel electrode for an alkaline secondary battery according to the present invention includes a positive electrode core material and a positive electrode mixture filled in the positive electrode core material, the positive electrode mixture including nickel hydroxide as a positive electrode active material, the nickel hydroxide including a sulfate, and the weight ratio of the S component included in the sulfate to the Ni component in the nickel hydroxide is 0.28% or more and 1.50% or less. The influence of the memory effect of the alkaline secondary battery can be reduced by the weight ratio of the S component included in the sulfate in the nickel hydroxide being 0.28% or more and 1.50% or less to the Ni component. Therefore, according to the present invention, it is possible to provide a nickel electrode for an alkaline secondary battery capable of reducing the influence of the memory effect, and an alkaline secondary battery including this nickel electrode. [Brief description of the drawings]
[0015] [Figure 1] 1 is a cross-sectional view that shows a schematic configuration of a nickel-metal hydride secondary battery according to an embodiment of the present invention. [Diagram 2] 1 is a graph showing discharge curves before and after a partial charge / discharge test in Example 1. [Diagram 3] 1 is a graph showing discharge curves before and after a partial charge / discharge test of Comparative Example 1. [Figure 4] 1 is a drawing-substitute photograph showing a secondary electron image by SEM of the positive electrode active material powder of Example 2. [Diagram 5] 1 is a graph showing the relationship between the ratio of S to Ni (S / Ni) and the voltage drop (ΔV) during remaining discharge. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] An alkaline secondary battery to which the present invention is applied will be described below with reference to the drawings. Although the alkaline secondary battery to which the present invention is applied is not particularly limited, for example, the case where the present invention is applied to a single-plate type nickel-hydrogen secondary battery (hereinafter, simply referred to as a battery) 2 as shown in FIG. 1 will be described as an example.
[0017] As shown in Fig. 1, the battery 2 includes a sealable container 10 made of acrylic resin. An electrode group 6 is disposed in the container 10 together with an alkaline electrolyte 4. As the alkaline electrolyte 4, an electrolyte that is generally used in nickel-metal hydride secondary batteries is preferably used. For example, it is preferable to use an alkaline electrolyte that contains KOH, NaOH, and LiOH as solutes.
[0018] The electrode group 6 is formed by sandwiching one positive electrode (nickel electrode) 14 between two negative electrodes 12 insulated by a separator 8. A positive electrode lead 16 is attached to the positive electrode 14, and this positive electrode lead 16 extends to the outside of the container 10 through a positive electrode lead through hole 20 provided in the upper wall 18 of the container 10. In addition, a negative electrode lead 22 is attached to the negative electrode 12, and this negative electrode lead 22 extends to the outside of the container 10 through a negative electrode lead through hole 24 provided in the upper wall 18 of the container 10. Note that the positive electrode lead through hole 20 and the negative electrode lead through hole 24 are liquid-tight.
[0019] The container 10 has a female screw hole 28 formed in one side wall 26, and a pressurizing screw 30 that fits into the female screw hole 28 is disposed therein. An acrylic resin pressurizing plate 32 is disposed at the tip of the pressurizing screw 30. The pressurizing plate 32 holds the above-mentioned electrode group 6 between itself and the other side wall 34 of the container 10. When the pressurizing screw 30 is turned to advance into the container 10, the electrode group 6 can be pressurized via the pressurizing plate 32. The female screw hole 28 is also liquid-tight.
[0020] Next, the negative electrode 12 will be described in detail. The negative electrode 12 has a strip-shaped conductive negative electrode core, and a negative electrode mixture is held in this negative electrode core.
[0021] The negative electrode core is made of a sheet-like metal material with distributed through holes, and may be, for example, a punched metal sheet or a sintered substrate made by molding and sintering metal powder. The negative electrode mixture is not only filled into the through holes of the negative electrode core, but is also held in layers on both sides of the negative electrode core.
[0022] The negative electrode mixture contains hydrogen storage alloy particles capable of absorbing and releasing hydrogen as a negative electrode active material, a conductive material, and a binder. The binder functions to bind the hydrogen storage alloy particles, the negative electrode additive, and the conductive material to each other, and at the same time, to bind the negative electrode mixture to the negative electrode core. Here, a hydrophilic or hydrophobic polymer or the like can be used as the binder, and carbon black or graphite can be used as the conductive material. The negative electrode additive is added as necessary.
[0023] The hydrogen storage alloy in the hydrogen storage alloy particles is not particularly limited, and it is preferable to use one that is used in a general nickel-hydrogen secondary battery. More preferably, a rare earth-Mg-Ni based hydrogen storage alloy is used. The composition of this rare earth-Mg-Ni based hydrogen storage alloy can be freely selected, but for example, a rare earth-Mg-Ni based hydrogen storage alloy having the general formula: Ln 1-a Mg a Ni b-c-d Al c M d (I) It is preferable to use one represented by the following formula:
[0024] In general formula (I), Ln represents at least one element selected from the group consisting of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, Y, Zr, and Ti; M represents at least one element selected from the group consisting of V, Nb, Ta, Cr, Mo, Mn, Fe, Co, Ga, Zn, Sn, In, Cu, Si, P, and B; and the subscripts a, b, c, and d represent numbers satisfying the relationships 0.01≦a≦0.30, 2.8≦b≦3.9, 0.05≦c≦0.30, and 0≦d≦0.50, respectively.
[0025] Next, the above-mentioned hydrogen storage alloy particles can be obtained, for example, as follows. First, metal raw materials are weighed and mixed to obtain a desired composition, and the mixture is melted, for example, in an induction melting furnace, and then cooled to form an ingot. The resulting ingot is subjected to a heat treatment in an inert gas atmosphere at 900 to 1200°C for 5 to 24 hours. The ingot is then cooled to room temperature, crushed, and sieved to obtain hydrogen storage alloy particles of the desired particle size.
[0026] The negative electrode 12 can be produced, for example, as follows. First, a negative electrode mixture paste is prepared by kneading a hydrogen storage alloy powder, which is an aggregate of hydrogen storage alloy particles, a conductive material, a binder, and water. The obtained negative electrode mixture paste is applied to a negative electrode core and dried. After drying, the negative electrode core to which the hydrogen storage alloy particles and the like are attached is rolled and cut. In this way, the negative electrode 12 is produced. Then, a negative electrode lead 22 is connected to a predetermined position of the negative electrode 12.
[0027] The obtained negative electrode 12 is wrapped in a separator 8. Here, as the material of the separator 8, for example, a polyamide fiber nonwoven fabric to which a hydrophilic functional group has been added, or a polyolefin fiber nonwoven fabric such as polyethylene or polypropylene to which a hydrophilic functional group has been added can be used. Specifically, it is preferable to use a nonwoven fabric mainly made of polyolefin fibers to which a sulfonation treatment has been applied to add a sulfonic group. Here, the sulfonic group is added by treating the nonwoven fabric with an acid containing a sulfonic group, such as sulfuric acid or fuming sulfuric acid. A battery using a separator 8 containing such fibers having a sulfonic group exhibits excellent self-discharge characteristics.
[0028] Next, the positive electrode 14 will be described in detail. The positive electrode 14 includes a conductive positive electrode core material having a porous structure, and a positive electrode mixture held within the pores of the positive electrode core material.
[0029] As such a positive electrode core material, for example, a nickel-plated mesh-like, sponge-like or fibrous metal body, or nickel foam can be used.
[0030] The positive electrode mixture contains a positive electrode active material, a conductive material, a positive electrode additive, and a binder. The binder functions to bind the positive electrode active material, the conductive material, and the positive electrode additive, and also to bind the positive electrode mixture to the positive electrode core material. Examples of the binder that can be used here include carboxymethylcellulose, methylcellulose, PTFE (polytetrafluoroethylene) dispersion, and HPC (hydroxypropylcellulose) dispersion.
[0031] Examples of conductive materials include cobalt oxide (CoO) and cobalt hydroxide (Co(OH) 2 One or more conductive materials selected from cobalt compounds such as ruthenium oxide, cobalt (Co), and cobalt (Co) can be used. The conductive material is added to the positive electrode mixture as necessary, and may be added in the form of a powder or in the form of a coating that covers the surface of the positive electrode active material and is included in the positive electrode mixture.
[0032] The positive electrode additive is added as necessary to improve the characteristics of the positive electrode, and for example, yttrium oxide, zinc oxide, etc. can be used.
[0033] Nickel hydroxide is used as the positive electrode active material. This nickel hydroxide contains sulfate, specifically SO 4 The weight ratio of this sulfate to the Ni component in the nickel hydroxide is preferably set to 14.3% or more and 30% or less.
[0034] Here, sulfate is generated in the manufacturing process of nickel hydroxide, which will be described later, but since it is not a substance directly involved in the battery reaction, it has been removed as much as possible. However, as a result of intensive research by the present inventors on reducing the memory effect of alkaline secondary batteries, they have found that the inclusion of sulfate, which has been reduced as much as possible in the past, in a larger amount than before has a favorable effect on reducing the memory effect. Specifically, when the S component contained in the sulfate is contained in the nickel hydroxide at a weight ratio of 0.28% or more relative to the Ni component, the memory effect is reduced. In other words, the more the weight ratio of the S component to the Ni component in the nickel hydroxide is greater than 0.28%, the greater the effect of reducing the memory effect. However, when the S component contained in the sulfate exceeds 1.50% relative to the Ni component in the nickel hydroxide, the capacity of the positive electrode decreases significantly, so the upper limit of the S component contained in the sulfate is set to 1.50% or less.
[0035] The method for producing the positive electrode active material is, for example, carried out in the following procedure. First, a weighed amount of nickel sulfate is added to water to prepare an aqueous solution containing nickel sulfate. Next, while stirring the obtained aqueous solution, an aqueous solution of sodium hydroxide is gradually added to cause a reaction, thereby precipitating nickel hydroxide particles. Here, it is preferable to dissolve Al in the nickel hydroxide. When dissolving Al in the solid solution, nickel sulfate and aluminum sulfate are weighed so as to obtain a predetermined composition and added to water to prepare a mixed aqueous solution containing nickel sulfate and aluminum sulfate.
[0036] Next, while stirring the resulting mixed aqueous solution, sodium hydroxide aqueous solution is gradually added and reacted to precipitate particles mainly composed of nickel hydroxide and containing aluminum as a solid solution. In this way, Ni(OH) 2 The particles are Ni(OH) with Al as a solid solution. 2 The particles have an α-type crystal structure, and since relatively large spaces are formed in the crystal structure, they can contain a large amount of sulfate.
[0037] In addition, Ni(OH) 2 It is preferable to further dissolve Yb, Co, etc. in the aqueous solution. In order to dissolve these elements in the aqueous solution, ytterbium sulfate and cobalt sulfate are also added to prepare the above-mentioned mixed aqueous solution.
[0038] The positive electrode 14 can be produced, for example, as follows. First, a conductive material, a positive electrode additive, water, and a binder are added to the positive electrode active material powder obtained as described above, which is an aggregate of particles of the positive electrode active material, and the mixture is kneaded to prepare a positive electrode mixture slurry. The obtained positive electrode mixture slurry is filled into, for example, a foamed nickel, and dried. After drying, the foamed nickel filled with nickel hydroxide particles and the like is rolled and then cut. This results in a positive electrode 14 carrying the positive electrode mixture. Then, a positive electrode lead 16 is connected to a predetermined position of the positive electrode 14.
[0039] A predetermined number of the positive electrodes 14 obtained as described above are prepared, and a predetermined number of the negative electrodes 12 in which the separators 8 obtained as described above are combined are prepared. Then, a laminate is formed in a state in which one positive electrode 14 is sandwiched between two negative electrodes 12, to obtain an electrode group 6. This electrode group 6 is disposed between the other side wall 34 and the pressing plate 32 in the container 10. Then, the electrode group 6 is held in the container 10 in a pressurized state by turning the pressure screw 30. Subsequently, a predetermined amount of the alkaline electrolyte 4 is injected into the container 10. Then, the container 10 containing the electrode group 6 and the alkaline electrolyte 4 is sealed by a rubber seal (not shown). At this time, the positive electrode lead 16 is disposed so as to extend to the outside of the container 10 through the positive electrode lead through hole 20, and the negative electrode lead 22 is disposed so as to extend to the outside of the container 10 through the negative electrode lead through hole 24. In this manner, the battery 2 according to the present invention is obtained. The obtained battery 2 is subjected to an initial activation process and is made ready for use.
[0040] [Example] 1. Battery manufacturing Example 1
[0041] (1) Manufacturing of positive electrodes Nickel sulfate, aluminum sulfate, and ytterbium sulfate as starting raw materials were weighed to obtain a predetermined composition. The weighed nickel sulfate, aluminum sulfate, and ytterbium sulfate were added to a 1 mol / l aqueous sulfuric acid solution to prepare a mixed aqueous solution. While stirring the resulting mixed aqueous solution, a 10 mol / l aqueous sodium hydroxide solution was gradually added to the mixed aqueous solution to cause a reaction, and the pH during the reaction was stabilized at 13 to 14 to generate nickel hydroxide particles mainly composed of nickel hydroxide and containing Al and Yb as a solid solution. As a result, a nickel hydroxide powder (positive electrode active material powder) was obtained, which is an aggregate of nickel hydroxide particles containing Al and Yb as a solid solution.
[0042] A portion of the resulting nickel hydroxide was set aside as a sample for composition analysis and a sample for crystal structure analysis, and the remainder was used for producing positive electrodes.
[0043] Here, the composition of the sample for composition analysis was analyzed using a high-frequency inductively coupled plasma (ICP) optical emission spectrometer, and the results were Ni 41.9%, Al 3.81%, Yb 7.38%, sulfate (SO 4 ) was confirmed to be 10.20%. From this result, it was confirmed that the ratio of sulfate (SO 4 The ratio of sulfate (SO 4 ) is formed from the starting raw materials and the aqueous sulfuric acid solution in the above-mentioned manufacturing process.
[0044] Next, X-ray diffraction (XRD) analysis was performed on the samples for crystal structure analysis. A powder XRD device (MiniFlex600 manufactured by Rigaku) was used for the analysis. The analysis conditions were as follows: X-ray source: CuKα, tube voltage: 40 kV, tube current: 15 mA, scan speed: 5 degrees / min, step width: 0.02 degrees. From the profile of the analysis results, it was found that nickel hydroxide has an α-type crystal structure, Ni(OH) 2 It was confirmed that.
[0045] Next, 7 parts by weight of cobalt hydroxide powder, 0.104 parts by weight of HPC (hydroxypropyl cellulose) powder, 0.28 parts by weight of PTFE (polytetrafluoroethylene) powder, and 78 parts by weight of water were added to 100 parts by weight of the positive electrode active material powder obtained as described above, and these were kneaded to prepare a slurry of a positive electrode mixture. The obtained slurry of the positive electrode mixture was filled into a sheet-shaped foamed nickel as a positive electrode core material. Then, the slurry of the positive electrode mixture filled into the foamed nickel was dried. Then, the foamed nickel filled with the positive electrode mixture was rolled to increase the amount of the positive electrode active material per unit volume, and then cut into a square shape of 30 mm in length and 30 mm in width to obtain a positive electrode (nickel electrode) 14. The thickness of this positive electrode 14 is 0.80 mm. In addition, a positive electrode lead 16 was welded to a part of the positive electrode 14. The capacity of this positive electrode 14 was 300 mAh.
[0046] (2) Manufacturing of negative electrodes First, La, Sm, Zr, Mg, Ni, and Al were weighed and mixed in the specified ratios. The mixture was melted in a high-frequency induction melting furnace in an argon gas atmosphere, and the molten metal was poured into a mold and cooled to room temperature to produce an ingot of hydrogen storage alloy.
[0047] The ingot was then subjected to a heat treatment in an argon gas atmosphere at 1000°C for 10 hours. After the heat treatment, the hydrogen storage alloy ingot was cooled to room temperature and mechanically pulverized in an argon gas atmosphere to obtain a powder of hydrogen storage alloy particles. The obtained powder was sieved to obtain a hydrogen storage alloy powder of a predetermined particle size. The particle size of the obtained hydrogen storage alloy powder was measured using a laser diffraction / scattering particle size distribution measurement device, and the volume average particle size (MV) of the hydrogen storage alloy particles was found to be 65 μm.
[0048] A sample taken from this hydrogen storage alloy powder was placed in an emission spectrometer and the composition was analyzed by ICP emission spectroscopic analysis. As a result, the composition of the hydrogen storage alloy was 0.30 Sm 0.69 Zr 0.01 ) 0.89 Mg0.11 Ni 3.33 Al 0.17 It was.
[0049] To 100 parts by weight of the obtained hydrogen storage alloy powder, 0.2 parts by weight of sodium polyacrylate, 0.04 parts by weight of carboxymethyl cellulose, 1.5 parts by weight of a dispersion of styrene-butadiene rubber (SBR) with a solid content of 50%, 0.3 parts by weight of carbon black, and 22.4 parts by weight of water were added and kneaded to prepare a paste of a negative electrode mixture.
[0050] Next, the negative electrode mixture paste was applied evenly and to a uniform thickness on both sides of a perforated iron plate as a negative electrode core. The perforated plate had a thickness of 60 μm, and its surface was nickel-plated. The perforated plate was also filled with the negative electrode mixture paste. In this way, a negative electrode intermediate product was manufactured.
[0051] After drying the paste, the intermediate product of the negative electrode holding the hydrogen storage alloy powder was further rolled to increase the amount of alloy per volume, and then cut into a length of 35 mm and a width of 35 mm to obtain the negative electrode 12. Here, the thickness of the negative electrode was 0.25 mm. The capacity of the negative electrode was 540 mAh.
[0052] (3) Assembly of nickel-metal hydride secondary batteries One positive electrode 14 and two negative electrodes 12 obtained as described above were prepared. The negative electrode 12 was wrapped in a separator 8. The negative electrodes 12 wrapped in separators 8 were then arranged on both sides of the positive electrode 14 and combined to form an electrode group 6. Here, the separator 8 was made of a nonwoven fabric made of polypropylene fibers that had been subjected to a sulfonation treatment, and had a thickness of 0.16 mm (basis weight 55 g / m 2 This electrode group 6 was disposed between the press plate 32 and the other side wall 34 inside the container 10. Then, the pressure screw 30 was turned to press down the electrode group 6 with a torque of 20 kgf·cm.
[0053] Meanwhile, an alkaline electrolyte (9.4N) consisting of an aqueous solution containing KOH, NaOH and LiOH was prepared.
[0054] Next, a predetermined amount of the prepared alkaline electrolyte was poured into the container 10. Thereafter, the container 10 was sealed with a rubber seal (not shown), and the nickel-metal hydride secondary battery 2 was assembled.
[0055] (4) Initial activation process Battery 2 was left to stand for 12 hours in an environment at a temperature of 60° C. Thereafter, the positive electrode capacity (300 mAh) was set to 1 It, and after charging at 0.02 It for 5 hours, it was subsequently charged at 0.10 It for 15 hours, and then discharged at 0.2 It until the battery voltage reached 1.0 V. This initial activation process allowed Battery 2 to be in a usable state.
[0056] Example 2 A nickel-metal hydride secondary battery was manufactured in the same manner as in Example 1, except that ytterbium sulfate was excluded from the starting raw materials when manufacturing the positive electrode active material, and the solid solution element was changed to only Al. The composition of the positive electrode active material in Example 2 was analyzed by ICP, and the results were 43.7% Ni, 5.02% Al, and 9.00% sulfate. Therefore, the ratio of sulfate to Ni in the positive electrode active material in Example 2 was 9.00 / 43.7=20.6%.
[0057] Example 3 A nickel-hydrogen secondary battery was manufactured in the same manner as in Example 1, except that ytterbium sulfate was excluded from the starting raw materials when manufacturing the positive electrode active material, and instead cobalt sulfate was added, so that the solid solution elements were Al and Co. The composition of the positive electrode active material in Example 3 was analyzed by ICP, and the results were Ni 42.3%, Al 3.60%, Co 2.57%, and sulfate 6.84%. Therefore, the ratio of sulfate to Ni in the positive electrode active material in Example 3 was 6.84 / 42.3=16.2%.
[0058] Example 4 A nickel-hydrogen secondary battery was manufactured in the same manner as in Example 1, except that ytterbium sulfate was removed from the starting raw materials when manufacturing the positive electrode active material, manganese sulfate was added instead, and the solid solution elements were changed to Al and Mn. The composition of the positive electrode active material in Example 4 was analyzed by ICP, and the results were Ni 44.3%, Al 3.83%, Mn 2.54%, and sulfate 6.72%. Therefore, the ratio of sulfate to Ni in the positive electrode active material in Example 4 is 6.72 / 44.3=15.2%.
[0059] Example 5 A nickel-hydrogen secondary battery was manufactured in the same manner as in Example 1, except that ytterbium sulfate was excluded from the starting raw materials when manufacturing the positive electrode active material, the solid solution element was changed to only Al, and the amount of Al was reduced to 3.92% compared to Example 1. The composition of the positive electrode active material in Example 5 was analyzed by ICP, and the results were Ni 48.7%, Al 3.92%, and sulfate 6.98%. Therefore, the ratio of sulfate to Ni in the positive electrode active material in Example 5 was 6.98 / 48.7=14.3%.
[0060] Example 6 A nickel-hydrogen secondary battery was manufactured in the same manner as in Example 3, except that the amount of cobalt sulfate added to the starting raw material was adjusted, and the amount of this sulfate was increased to 8.26% compared to Example 3. The composition of the positive electrode active material in Example 6 was analyzed by ICP, and the results were Ni 42.6%, Al 3.57%, Co 5.35%, and sulfate 8.26%. Therefore, the ratio of sulfate to Ni in the positive electrode active material in Example 6 is 8.26 / 42.6=19.4%.
[0061] Comparative Example 1 A nickel-hydrogen secondary battery was manufactured in the same manner as in Example 1, except that aluminum sulfate and ytterbium sulfate were excluded from the starting raw materials when manufacturing the positive electrode active material, and instead cobalt sulfate and zinc sulfate were added, so that the solid solution elements were Co and Zn. The composition of the positive electrode active material in Comparative Example 1 was analyzed by ICP, and the results were Ni 53.0%, Co 0.64% (excluding surface Co), Zn 4.36%, and sulfate 0.19%. Therefore, the ratio of sulfate to Ni in the positive electrode active material in Comparative Example 1 was 0.19 / 53.0=0.4%.
[0062] 2. Battery evaluation (1) Capacity inspection After the activation treatment, the batteries of Examples 1 to 6 and Comparative Example 1 were repeatedly charged at 0.1 It for 16 hours in a 25° C. environment and then discharged at 0.2 It until the battery voltage reached 1.0 V, until the positive electrode capacity reached its maximum.
[0063] (2) Partial charge / discharge test After the positive electrode capacity reached its maximum capacity, the battery was charged at 0.1 It for 12 hours, and then completely discharged at 0.1 It (until the battery voltage reached 1.0 V) (initial discharge). Next, a charge-discharge cycle of SOC 50% to 110% was repeated to intentionally reproduce the memory effect. The details are as follows.
[0064] First, the battery was charged at 0.1 It for 12 hours, then discharged at 1.0 C for 0.5 hours (until the battery voltage reached 1.0 V), and charged at 1.0 C for 0.6 hours. This cycle of charge and discharge was repeated 5 times. The battery was then completely discharged (remaining discharge) at 0.1 It (until the battery voltage reached 1.0 V).
[0065] For the batteries of Examples 1 to 6 and Comparative Example 1, the battery voltage at the time of initial discharge, the battery voltage at the time of remaining discharge, and the difference between the battery voltage at the time of initial discharge and the battery voltage at the time of remaining discharge (hereinafter referred to as voltage drop at remaining discharge ΔV or simply ΔV) were determined, and each value is shown in Table 1. ΔV was calculated from the difference between the battery voltage at the time of initial discharge and the battery voltage at the time of remaining discharge at SOC 40% (depth of discharge 60%).
[0066] Furthermore, for Example 1 and Comparative Example 1, discharge curves showing the relationship between the battery voltage and the battery capacity during initial discharge and discharge curves showing the relationship between the battery voltage and the battery capacity during remaining discharge are shown in Figures 2 and 3.
[0067] 3. Analysis of Ni and S The batteries of Examples 1 to 6 and Comparative Example 1 after the battery evaluation were disassembled, and the positive electrodes were taken out from the inside. The taken-out positive electrodes were washed with water and then left in a vacuum dryer for 12 hours to be completely dried. The positive electrodes after the drying process were separated into a positive electrode core material and a positive electrode active material using an ultrasonic homogenizer, and then passed through a sieve with a mesh size of 45 μm to remove the positive electrode core material and collect the positive electrode active material powder. The collected positive electrode active material powder was subjected to surface observation with a scanning electron microscope (SEM) and elemental analysis with energy dispersive X-ray spectroscopy (EDS), that is, elemental analysis was performed by so-called SEM / EDS. The accelerating voltage at this time was 15 keV.
[0068] From the SEM image of the analysis result, a mapping analysis of the entire area was performed by EDS. At this time, the magnification was 1000 times. At this magnification, several tens of active material particles can be confirmed in the field of view. Here, as an example, a secondary electron image of the positive electrode active material powder of Example 2 by SEM is shown in FIG. 4. Furthermore, the analysis results of the elements that could be detected for Examples 1 to 6 and Comparative Example 1 are shown in Table 2. Note that oxygen and carbon were excluded from the analysis.
[0069] From the obtained analysis results, the ratio of S component contained in sulfate to Ni (S / Ni [%]) in the particles of nickel hydroxide (positive electrode active material) was calculated. The obtained results are shown in Tables 1 and 2. Moreover, the relationship between S / Ni and ΔV shown in Table 1 is shown in FIG.
[0070] [Table 1]
[0071] [Table 2]
[0072] 4. Discussion From FIG. 2 and FIG. 3, which respectively show the discharge curves at the initial discharge and the residual discharge after partial charge and discharge of Example 1 and Comparative Example 1, it can be seen that the battery voltage drops during discharge and the discharge capacity also drops during the residual discharge compared to the initial discharge. This is due to the memory effect. From the results of Table 1 and FIG. 5, the following can be seen. Comparative Example 1, in which the active material contains almost no sulfate and the ratio of the S component to Ni is extremely low, has a voltage drop ΔV value of 0.0132V during the residual discharge. In contrast, Examples 1 to 6, in which the ratio of the S component to Ni is higher than that of Comparative Example 1, have a voltage drop ΔV value of 0.0085V or less during the residual discharge, and the influence of the voltage drop is reduced. In other words, it was found that the influence of the voltage drop in Examples 1 to 6 is reduced to about half that of Comparative Example 1. From this, it can be said that the influence of the voltage drop due to the memory effect can be reduced by setting the ratio of the S component contained in the sulfate to Ni in the nickel hydroxide particles to 0.28% or more. The effect of reducing the voltage drop caused by the memory effect has been achieved up to a ratio of S to Ni of 1.50%. However, if the ratio of S contained in the sulfate to Ni in the nickel hydroxide particles exceeds 1.50%, the amount of sulfate that does not contribute to the battery reaction increases relatively, which may cause a decrease in battery capacity, so the ratio of S should be 1.50% or less.
[0073] The present invention is not limited to the above-described embodiment and examples, and various modifications are possible, for example, the alkaline secondary battery is not limited to a nickel-metal hydride secondary battery, and may be another alkaline secondary battery, and the mechanical structure is not particularly limited, and may be a single-plate battery, a cylindrical battery, a square battery, or the like. [Explanation of symbols]
[0074] 2. Nickel-metal hydride secondary battery 6 electrode groups 8 Separator 10 containers 12 Negative electrode 14 Positive electrode (nickel electrode)
Claims
1. The battery includes a positive electrode core material and a positive electrode mixture filled in the positive electrode core material, The positive electrode mixture contains nickel hydroxide, which is a positive electrode active material, and contains Al as a solid solution element. The nickel hydroxide contains a sulfate, A nickel electrode for an alkaline secondary battery, wherein a weight ratio of an S component contained in the sulfate to a Ni component in the nickel hydroxide is 0.28% or more and 1.50% or less.
2. A container and an electrode group accommodated in the container together with an alkaline electrolyte, The electrode group includes a positive electrode and a negative electrode combined with a separator interposed therebetween, The alkaline secondary battery according to claim 1 , wherein the positive electrode is a nickel electrode for an alkaline secondary battery.
3. 3. The alkaline secondary battery according to claim 2, wherein the negative electrode contains a hydrogen storage alloy.
Citation Information
Patent Citations
Nickel electrode active material for alkaline storage battery and nickel positive electrode using the same
JP1999238509A
Alkaline secondary battery positive electrode active material and alkaline secondary battery
JP1999329426A
Method of detecting refreshment of secondary battery
JP2001095167A
Alkaline storage battery and nickel electrode for alkaline storage battery, and active material powder for nickel electrode
JP2003249214A